PRELIMINARY RESULTS OF DOPPLER IMAGING ANALYSIS OF roAp STAR alpha Cir - Alentjev, D. V.; Mkrtichian, D. E. (Одеські астрономічні публікації, 2010)
Based on high-resolution spectra, we investigate the abundance distribution of chromium and silicon on the surface of alpha Cir using Doppler Imag ing technique. Results of our analysis show the pres ence of chromium and silicon spots on the surface of alpha Cir as well as large gradients of the abundances of these elements.